1990
DOI: 10.1161/01.res.67.3.636
|View full text |Cite
|
Sign up to set email alerts
|

Evidence against the "early protection-delayed death" hypothesis of superoxide dismutase therapy in experimental myocardial infarction. Polyethylene glycol-superoxide dismutase plus catalase does not limit myocardial infarct size in dogs.

Abstract: We previously found that superoxide dismutase (SOD) did not limit myocardial infarct size after 40 or 90 minutes of ischemia and 4 days of reperfusion in dogs. Because some other studies have shown limitation of infarct size after shorter periods of reperfusion, we postulated that our negative results might be due to late reperfusion injury mediated by superoxide anions produced after excretion of SOD. To test this "early protection-delayed death" hypothesis, we have examined whether SOD, conjugated to polyeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…However, the beneficial effect of scavengers or antioxidants during reperfusion is still controversial [33][34][35][36][37]. In our hands, when ROS production was mitigated by reperfunding the hearts in the presence of 2 mmol/L MPG (ROS scavenger), a reduction in IS of similar magnitude to that observed after cariporide was achieved (Fig.…”
Section: Resultsmentioning
confidence: 53%
“…However, the beneficial effect of scavengers or antioxidants during reperfusion is still controversial [33][34][35][36][37]. In our hands, when ROS production was mitigated by reperfunding the hearts in the presence of 2 mmol/L MPG (ROS scavenger), a reduction in IS of similar magnitude to that observed after cariporide was achieved (Fig.…”
Section: Resultsmentioning
confidence: 53%
“…However, in the dog model of ischemia-reperfusion using PEG-SOD, a long-acting form of SOD, infarct size was not reduced though the plasma SOD level was high during entire reperfusion periods (17). It has been reported recently that overexpression of extracellular SOD (EC-SOD), Cu, Zn-SOD and Mn-SOD induced by ischemic precondition have protective effects against myocardial ischemia-reperfusion injuries (18 -20, 34).…”
Section: Discussionmentioning
confidence: 99%
“…Conjugation of SOD with polyethylene glycol (PEG-SOD) had succeeded to prolong plasma half-life of SOD (16). Although administration of PEG-SOD resulted in high plasma concentration of SOD, no limitation of infarct size was observed in dog, which suggested superoxide anions accessible to circulating SOD, did not contribute to myocardial infarct size in ischemia-reperfusion (17). It has been recently reported that the heart of mice with overexpression of extracellular SOD (EC-SOD), which has high affinity to endothelial cells, underwent mild degrees of ischemia were less susceptible to the ischemia-reperfusion injuries than the heart of wild type mice (18).…”
mentioning
confidence: 99%
“…This possibility seems unlikely because we have shown recently that PMN influx after reperfusion primarily occurs during the first 3 hours and that no additional influx is detectable after 21 hours.32 Moreover, infarct size in untreated control dogs was not different when measured at 3, 6, or 24 hours of reperfusion.32 In another study, we found no difference between infarcts reperfused for 4 hours versus 4 days.33 In addition, we have found that treatment with polyethylene glycol-conjugated superoxide dismutase to achieve sustained anti-free radical treatment (and thereby prevent possible late reperfusion injury) did not limit myocardial infarct size after 90 minutes of ischemia. 34 In the present study, infarct size was measured by macrochemistry (TTC) after 3 hours of reperfusion and was based on two transverse slices of left ventricle. This method differs from that used in most of our previously reported studies of myocardial infarct size.21 '22,3435 In previous studies, we measured infarct size from detailed microscopic evaluation of five cross-sectional slices obtained 4 days after reperfusion, when the infarcts were fully developed.…”
Section: Effect Ofanti-cd18 Antibody On Myocardial Infarct Sizementioning
confidence: 99%